RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS THAILAND TERHADAP PERLAKUAN DOSIS PUPUK KUSUMA BIOPLUS DAN KNO3 PUTIH - Pamuji Setyo Utomo; Agus Suprianto (Jurnal Ilmiah Hijau Cendekia, 2019)
Shallot is an important vegetable commodity because it contains high nutrition, raw materials for medicines, as a complement to cooking spices, has lots of vitamins, and acts as an activator of enzymes in the body Average consumption of shallots per capita for 2011-2012 ranging between 2.36 kg / year and 2.74 kg / year. Development of shallot harvest, production and productivity in 2010-2017. Increasing the quality and yield of shallots in several constraints needs to be considered, among others, the provision of nutrients for plants through fertilization. The purpose of this study was to determine the interaction effects of Kusuma BioPlus compost treatment and KNO3 White fertilizer on growth and production of Thai Onion (Allium ascalonicum L.) varieties. This research was conducted in May 2016 until July 2016 in Kediri Begendul Hamlet, Sidowarek Village, Plemahan Subdistrict. Place height 1000 asl, soil pH 6, Type of sandy clay soil. The results showed that there was no real interaction between the dosage of Kusuma Bioplus fertilizer and KNO3 fertilizer on the number of leaves, plant height, number of tubers, clump wet weight and weight of dried tubers storing age groups 4 days after harvest. From the results of the study there was a single reaction to the number of leaves, plant height, tuber number, clump wet weight, and weight of dry tubers storing 4-day age groups after harvest from white KNO3 fertilizer with 15 t/ ha and 450 kg / ha by obtaining store dried shallots as much as 9.3 gr / plant, equivalent to 9.3 t / ha